Effects of fatigue on the kinematic hands symmetry in freestyle - Aujouannet, Y. A.; Rouard, A. H.; Bonifazi, M. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to investigate the effects of an exhaustive test on the symmetry of right and left hands trajectories. Eight male international swimmers performed 25 m in 1/2 tethered swimming at maximal velocity to calculate power before and after an exhaustive test of 4*50m freestyle. Right and left fingertips were digitised frame by frame from underwater views (50Hz). The trajectories were characterised by different points in the frontal plane (O), (I) and the sagittal plane (F),(D) et (B) to calculate the symmetry index.(SI) based on the differences right-left coordinates. The spatial symmetry and the temporal asymmetry observed for all the points was maintained after the exhaustive test. The stable spatial symmetry with fatigue could be related to the high level of the population. The temporal asymmetry was not associated to the breathing side or to the dominant hand and could reflect the individual force-time patterns within the stroke.